Introduction of DNA Based Paternity Determinations in Turkey - Vural, Burçak; Atlıoğlu, Eyüp; Özbek, Uğur; Büyükdevrim, Sevim; Kolusayın, Özdemir; Özçelik, Tayfun (The Bulletin of Legal Medicine, 2002)
DNA analysis for paternity determination has been in use since March 1993 in Turkey. This was accomplished with the collaboration of Istanbul University, Institute for Experimental Medicine (DETAM) and Council of Forensic Medicine, Ministry of Justice. The allele and genotype frequencies of six genomic loci (HLADQA1, LDLR, GYPA, HBGG, D7S8 and GC) have been determined in the Turkish population. These six polymorphic loci were used in the analysis of 96 cases of disputed paternity. In 26 of these 96 cases, the putative father was excluded. In 12 of these 26 cases, exclusion was possible by DNA analysis alone. It is striking that in three of these DNA-based exclusions, phenotype analysis alone resulted in attribution of the paternity with 99.90 %, 99.87 % and 99.82% certainty. In the remaining 70 cases for whom paternity could not be excluded either by DNA or phenotype analyses, paternity index values were determined. Attribution of the paternity was done with over 99.73 % certainty in 68 cases. Key words: DNA analysis, paternity, PCR, HLADQA1, LDLR, GYPA, HBGG, D7S8, GC